2021
DOI: 10.24315/tred.623999
|View full text |Cite
|
Sign up to set email alerts
|

Li̇sansüstü Öğrenci̇leri̇ni̇n Stem Eği̇ti̇mi̇ İle İlgi̇li̇ Görüşleri̇: İki̇ Üni̇versi̇te Örneği̇

Abstract: Bu araştırmanın amacı lisansüstü öğrencilerinin STEM eğitimi ile ilgili görüşlerini belirlemektir. Araştırmanın yöntemi durum çalışmasıdır. Araştırmanın çalışma grubu iki farklı üniversitenin fen bilgisi eğitimi ana bilim dalında lisansüstü eğitim gören toplam 10 öğrenciden oluşmaktadır. Veri toplama aracı olarak 10 sorudan oluşan yarı yapılandırılmış mülakat kullanılmıştır. Mülakatlardan elde edilen veriler içerik analizine göre çözümlenmiştir. Verilerin analizinde "STEM ile ilgili tanımlar", "STEM eğitiminin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…These are the insufficient readiness of the students, difficulty in group work and lack of motivation, lack of materials, unsuitable physical conditions of the classroom, and the attitude of school administrators and parents. The findings are compatible with some studies in the literature (Alagöz and Sözen, 2021;Bakırcı and Kutlu, 2018;Bozkurt Altan et al, 2016;Karslı Baydere et al, 2021;Niess, 2005;Özçakır et al, 2016). Some suggestions were made in line with the results of the study.…”
Section: Resultssupporting
confidence: 92%
“…These are the insufficient readiness of the students, difficulty in group work and lack of motivation, lack of materials, unsuitable physical conditions of the classroom, and the attitude of school administrators and parents. The findings are compatible with some studies in the literature (Alagöz and Sözen, 2021;Bakırcı and Kutlu, 2018;Bozkurt Altan et al, 2016;Karslı Baydere et al, 2021;Niess, 2005;Özçakır et al, 2016). Some suggestions were made in line with the results of the study.…”
Section: Resultssupporting
confidence: 92%
“…Many studies are carried out in line with these issues. However, considering STEM research in graduate education, which is thought not to be mentioned enough among the studies, various studies were found (Feldon, Shukla and Maher, 2016;Karslı-Baydere, Şahin-Çakır, Hacıoğlu and Kocaman, 2021;Love-Stowell, et al, 2015;Olson, Hergatt-Huffman and Litson, 2020). These studies examined; It reveals that the education to be given in the development of research skills of graduate students in STEM fields is important, that the understanding and studies towards STEM education should be increased, and that the training of the trainers who will lead these studies should be given importance.…”
Section: Introductionmentioning
confidence: 99%